Acceptability of a Self-Help Programme to Address the Use of Indecent Images of Children - Sarah Wefers; Alexandra Bailey; Nadia Rasooli; Donald Findlater; Lucy Allen (Sexual Offending)
The use of indecent images of children (IIOC) is of continued concern and growing prevalence. A multi-agency approach to this online crime is necessary, as it cannot be eradicated by law enforcement alone. Previous research has examined the pathways to offending for this population, and prevention strategies that could be used to deter offending in the first instance, or to stop behaviour once it has begun. The current qualitative study aimed to explore acceptability of a prevention initiative; a self-help focussed service (a website and calls with a professional). Semi-structured interviews with eight individuals who had accessed IIOC and engaged in this self-help focussed service were conducted. Transcripts were analysed using qualitative framework approach, using the Theoretical Framework of Acceptability (TFA) domains as deductive codes. All seven domains of the TFA were identified in the transcripts, indicating the applicability of the framework. Overall, participants reported mixed acceptability of and satisfaction with the self-help programme and calls with practitioners, but high perceived effectiveness in the service supporting them stop their illegal behaviours. The implications of the study are considered in line with improvements that could be made to this existing self-help prevention initiative.